Affinity for Poetry and Aesthetic Appreciation of Joyful and Sad Poems - Kraxenberger, Maria; Menninghaus, Winfried (Frontiers in Psychology, 2017)
Artworks with sad and affectively negative content have repeatedly been reported to elicit positive aesthetic appreciation. This topic has received much attention both in the history of poetics and aesthetics as well as in recent studies on sad films and sad music. However, poetry and aesthetic evaluations of joyful and sad poetry have received only little attention in empirical studies to date. We collected beauty and liking ratings for 24 sad and 24 joyful poems from 128 participants. Following previous studies, we computed an integrated measure for overall aesthetic appreciation based on the beauty and liking ratings to test for differences in appreciation between joyful and sad poems. Further, we tested whether readers’ responses are related to their affinity for poetry. Results show that sad poems are rated significantly higher for aesthetic appreciation than joyful poems, and that aesthetic appreciation is influenced by the participants’ affinity for poetry.